2023
DOI: 10.3390/s23062887
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Early Noninvasive COVID-19 Detection Using Electronic-Nose Technologies and Disease-Specific VOC Metabolic Biomarkers

Abstract: The established efficacy of electronic volatile organic compound (VOC) detection technologies as diagnostic tools for noninvasive early detection of COVID-19 and related coronaviruses has been demonstrated from multiple studies using a variety of experimental and commercial electronic devices capable of detecting precise mixtures of VOC emissions in human breath. The activities of numerous global research teams, developing novel electronic-nose (e-nose) devices and diagnostic methods, have generated empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 196 publications
0
11
0
Order By: Relevance
“…The measurement system will be adapted to improve the control and sustainability of the management of the HVAC [68,79]. Finally, another promising improvement is the integration of a CO 2 sensor in a compact eNose, trained to operate fully as an early non-invasive detector of airborne transmitted pandemic outbreaks [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…The measurement system will be adapted to improve the control and sustainability of the management of the HVAC [68,79]. Finally, another promising improvement is the integration of a CO 2 sensor in a compact eNose, trained to operate fully as an early non-invasive detector of airborne transmitted pandemic outbreaks [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive review by Wilson and Forse [ 10 ] summarizes results from a wide range of recent international research studies that tested many types of e-nose devices and methods for their capabilities of COVID-19 detection in various healthcare situations and applications. A comparison of the differences in human symptom combinations vs. organs affected and deaths associated with COVID-19 disease vs. those associated with other prior viral pandemics in human history are elucidated.…”
Section: Review Of Special Issue Contributionsmentioning
confidence: 99%
“…The Wilson and Forse review [ 10 ] also suggested new ways in which e-nose data may be combined with corresponding chemical data (from the same clinical sample) that identifies COVID-19 specific disease biomarkers to increase, confirm, and strengthen the certainty of disease diagnoses. These types of analyses could be simultaneously carried out using dual-technology e-nose devices individually or in combination with instruments with VOC analytical chemistry capabilities.…”
Section: Review Of Special Issue Contributionsmentioning
confidence: 99%
“…Electronic nose systems can be used in a wide range of applications such as agriculture [18][19][20][21][22][23], environmental monitoring [24][25][26], food [27][28][29][30][31][32], quality control [33][34][35][36][37], military [38][39][40], and medical applications [41][42][43][44][45][46][47][48] like pharmaceutical, biomedical, disease and illness early detection, cosmetics, and numerous scientific research domains.…”
Section: Introductionmentioning
confidence: 99%